Auditory hallucinations in adults with hearing impairment: a large prevalence study. Issue 1 (20th March 2018) - Linszen, M. M. J.; van Zanten, G. A.; Teunisse, R. J.; Brouwer, R. M.; Scheltens, P.; Sommer, I. E.
Abstract: Background: Similar to visual hallucinations in visually impaired patients, auditory hallucinations are often suggested to occur in adults with hearing impairment. However, research on this association is limited. This observational, cross-sectional study tested whether auditory hallucinations are associated with hearing impairment, by assessing their prevalence in an adult population with various degrees of objectified hearing impairment. Methods: Hallucination presence was determined in 1007 subjects aged 18–92, who were referred for audiometric testing to the Department of ENT-Audiology, University Medical Center Utrecht, the Netherlands. The presence and severity of hearing impairment were calculated using mean air conduction thresholds from the most recent pure tone audiometry. Results: Out of 829 participants with hearing impairment, 16.2% ( n = 134) had experienced auditory hallucinations in the past 4 weeks; significantly more than the non-impaired group [5.8%; n = 10/173; p < 0.001, odds ratio 3.2 (95% confidence interval 1.6–6.2)]. Prevalence of auditory hallucinations significantly increased with categorized severity of impairment, with rates up to 24% in the most profoundly impaired group ( p < 0.001). The corrected odds of hallucination presence increased 1.02 times for each dB of impairment in the best ear. Auditory hallucinations mostly consisted of voices (51%), music (36%), and doorbells or telephones (24%). Conclusions: Our findings reveal that auditory hallucinations are common among patients with hearing impairment, and increase with impairment severity. Although more research on potential confounding factors is necessary, clinicians should be aware of this phenomenon, by inquiring after hallucinations in hearing-impaired patients and, conversely, assessing hearing impairment in patients with auditory hallucinations, since it may be a treatable factor.